PENGARUH MODAL PSIKOLOGIS DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL PADA SMA NEGERI KOTA DI KABUPATEN PATI - Wiwik Indarwati Iriana, 12.5202.0194; Fauzan, Muhamad (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze whether organizational commitment mediates the influence of psychological capital and professional competence on teachers performance in senior high shool state in Pati City. Sampling was done by census method so that all teachers who have civil servants working in the Senior High School in Pati City, amounting to 164 people used as a sample. Mechanical testing of the data used in this study include testing the validity of the factor analysis, reliability testing with Cronbach alpha formula, multiple regression analysis, and the significance test, the coefficient of determination to prove the truth of the research hypothesis and test mediation. The results showed that; psychological capital and professional competence significant effect on organizational commitment, psychological capital, professional competence and organizational commitment significantly influence the performance of teachers. However, commitment to the organization is not able to mediate the effect of psychological capital and professional competence onÂ teachers performance. Keywords: psychological capital, professional